Computer Modelling of the Information Properties of Hyper Chaotic Lorenz System and Its Application in Secure Communication System - Rusyn, Volodymyr; Mujiarto; Mamat, Mustafa; Azharul, Firmansyah; Sambas, Aceng; Dwipriyoko, Estiyan; Sutoni, Akhmad; Mada Sanjaya, W.S. (IOP Publishing, 2021)
This paper presents computer modeling, analysis and research of the hyper-chaotic Lorenz system based on programming interface that has been developed in LabView software environment. This study allows for generating and research of the main information properties of hyper-chaotic Lorenz system, focusing on time distribution of the four chaotic coordinates, phase portraits and Lyapunov exponents. The programming interface demonstrates the algorithm of masking and decrypt of the information carrier.
Keywords: Nonlinear; hyper-chaotic; Lorenz; LabView